Unsolved problems: Mesoscale polar cap flow channels’ structure, propagation, and effects on space weather disturbances - Lyons, Larry R.; Nishimura, Yukitoshi; Liu, Jiang; Zou, Ying; Bristow, William A.; Yadav, Sneha; Donovan, Eric; Nishitani, Nozomu; Shiokawa, Kazuo; Hosokawa, Keisuke (Frontiers in Astronomy and Space Sciences, 2023)
Dynamic mesoscale flow structures move across the open field line regions of the polar caps, and then enter the nightside plasma sheet where they can lead to important space weather disturbances, such as streamers, substorms, and omega bands. The polar cap structures have long durations (apparently at least ~1½ to 2 hours), but their connections to disturbances have received little attention. Moving forward, it will be important to uncover what causes these flow enhancement channels, how they map to the magnetospheric and magnetosheath structures, and what controls how they propagate across the polar cap and their dynamic effects after reaching the nightside auroral oval. The examples presented here use 630 nm auroral and radar observations and indicate that the motion of flow channels could be critical for determining when and where a particular disturbance within the nightside auroral oval will be triggered, and this could be included for full understanding of flow channel connections to disturbances. Also important is determining how polar cap flow channels lead to flow channels within the auroral oval, i.e., the plasma sheet, and determining the conditions along nightside oval/plasma sheet field lines that interact with an incoming flow polar-cap flow channel to give a particular disturbance. It will also be interesting to consider the generality of geomagnetic disturbances being related to connections with incoming polar cap flow channels, including the location, time, and type of disturbances, and whether the duration and expansion of disturbances is related to flow channel duration and to multiple flow channels.